(untitled) (Theatrum historiae, 2019)
This study deals with the residential network of Franz Joseph Czernin of Chudenitz (1697–1733), namely the urban part of this network. Czech count Czernin possessed many buildings in the capital cities of the historical lands of the Habsburg monarchy (eight in Prague, three in Vienna). Our goal is to discover this network and put it in the context of residential networks of Bohemian aristocrats in this period.